Primórdios da educação formal em Capivari do Sul nas décadas de 1950/1960: memórias de cotidianos, políticas e gestão - Nunes, Rosana Soares (Universidade do Vale do Rio dos Sinos, 2015)
The work brings up subjects of memories that, in the 1950s and 1960s, were students and teachers in rural school pioneer in terms of formal education of children in the municipality of Capivari do Sul/RS/Brasil. Through the narrative record, sought to perpetuate some of the many versions about experiences lived by the subjects involved in that school context. From the Oral History, the study mobilized some concepts related to memory, emphasizing that the facts narrated are not effectively described as indeed happened, since it is impossible the reconstruction at all. The work of the body is arranged in five parts. The first seeks to contextualize the scene of the narrative; the second and third parts deal on the theoretical field, memory and oral history, explaining also methodological issues of the interview. As the fourth and fifth chapters articulate oral narratives to theoretical and methodological framework, from some categories of analysis. The investigation brought to light similarities and discrepancies on them narrated issues, confirming some theoretician’s idea who deal with the subject memory: it is a matter of eternal modification as the experiences, now recollected by each interviewed. Working with oral narratives requires the clarity of its nonlinearity and the belief that memory is always crossed with memories and forgetfulness, being selective, fallible and sometimes even fanciful. Thus, the oral narratives analysis not release the sieve and filter historian and, like any other source requires methodological rigor. The study allowed to reveal significant aspects of the educational route in the city of Capivari do Sul, highlighting specific aspects of education policies in that area, as well as gender and school culture issues.
Keywords: Gestão; Políticas educacionais; Capivari do Sul/RS/Brasil; Memória; História oral; Management; Educational policies; Memory; Oral history; ACCNPQ::Ciências Humanas::Educação